Solar cell light absorption layer material, preparation method thereof and cell
By doping PbS quantum dots in inorganic perovskite materials to form a new solar cell light-absorbing layer material, the problems of taking into account both the stability and photoelectric conversion efficiency of the existing perovskite solar cell are solved, and higher photoelectric conversion efficiency and material stability are achieved.
Patent Information
- Application Number
- CN202311286229.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing perovskite solar cells cannot effectively take into account the stability and photoelectric conversion efficiency.
A new solar cell light-absorbing layer material is formed by doping PbS quantum dots into an inorganic perovskite material. This material includes inorganic perovskite materials such as CsPbCl3, CH3NH3PbI3, CsPbBr3, RbPbI3, and PbS quantum dots, and the doping concentration of PbS quantum dots is 50-100 mg/mL.
While ensuring the stability of all-inorganic perovskite materials, it can improve the photoelectric conversion efficiency and strengthen the stability of the material, thus solving the problem of taking into account both the stability and efficiency of existing perovskite solar cells.
Smart Images

Figure CN119815985A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell manufacturing, and in particular to a solar cell light absorption layer material and a preparation method thereof and a cell. Background Art
[0002] Currently, perovskite solar cells have also attracted much attention due to their many advantages such as low cost, wide absorption spectrum, high exciton binding energy and large absorption coefficient.
[0003] The light-absorbing layer in existing perovskite cells is made of organic-inorganic hybrid perovskite. Although it has high cell efficiency, its stability is poor. If inorganic perovskite materials are directly used to prepare solar cells, although the stability of the cell can be guaranteed, the photoelectric conversion efficiency of the cell will be significantly reduced. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a solar cell light absorbing layer material and a preparation method thereof and a cell, so as to solve the problem that the existing perovskite solar cells cannot effectively balance stability and photoelectric conversion efficiency.
[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:
[0006] The present invention provides a solar cell light-absorbing layer material, wherein the components constituting the light-absorbing layer material include an inorganic perovskite material and PbS quantum dots, and the PbS quantum dots are doped in the inorganic perovskite material.
[0007] Furthermore, in the light absorbing layer material, the doping concentration of the PbS quantum dots is 50 to 100 mg / mL.
[0008] Furthermore, in the light absorbing layer material, the inorganic perovskite material includes one or more of CsPbCl3, CH3NH3PbI3, CsPbBr3, and RbPbI3.
[0009] The present invention also provides a method for preparing a solar cell light absorbing layer material, which comprises:
[0010] Provide PbS quantum dots and cesium oleate precursor solutions;
[0011] Adding PbS quantum dots to the cesium oleate precursor solution and mixing well to obtain a precursor mixed solution;
[0012] In a protective gas atmosphere and under a heating state, the precursor mixed solution is injected into a lead halide solution for reaction, and then cooled, centrifuged and precipitated to obtain a solar cell light absorption layer material.
[0013] Furthermore, in the preparation method, the heating temperature is 140 to 200° C., and the reaction time is 90 to 150 seconds.
[0014] Furthermore, in the preparation method, the protective gas is argon.
[0015] Furthermore, in the preparation method, the PbS quantum dots are added to the cesium oleate precursor solution at a molar ratio of 0.8 to 2.5:1.
[0016] Furthermore, in the preparation method, before the precursor mixed solution is injected into the lead halide solution for reaction, the lead halide solution is heated to 140-200° C. with a temperature increase gradient of 2-10° C. / min.
[0017] Further, after obtaining the precipitate, the method further comprises:
[0018] The precipitate is added into n-hexane and ultrasonically dispersed, and then centrifuged to obtain the centrifuge liquid as the solar cell light absorption layer material.
[0019] The present invention also proposes a solar cell, which includes a transparent conductive electrode, an electron transport layer, a light absorbing layer, a hole transport layer and a counter electrode stacked in sequence, wherein the light absorbing layer is made of the above-mentioned solar cell light absorbing layer material.
[0020] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0021] In an embodiment of the present invention, the solar cell light absorption layer material provided comprises an inorganic perovskite material and PbS quantum dots, wherein the PbS quantum dots are doped in the inorganic perovskite material. Because the PbS quantum dots have good optical properties and a narrow spectral width, less energy can be converted into more ambient emission light. By doping the inorganic perovskite material with PbS quantum dots, the stability of the all-inorganic perovskite material can be ensured, and the surface defects can be passivated by using the PbS quantum dots, thereby improving the photoelectric conversion efficiency and further enhancing the stability of the material, thereby solving the problem that the existing perovskite solar cells cannot effectively balance the stability and photoelectric conversion efficiency.
[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a flow chart of a method for preparing a solar cell light absorbing layer material provided by an embodiment of the present invention;
[0024] Figure 2 This is a lattice structure analysis diagram of the light absorbing layer material prepared in Example 1;
[0025] Figure 3 is a lattice structure analysis diagram of the light absorbing layer material obtained in Example 1;
[0026] Figure 4 is a comparison chart of the PL spectrum intensity of the light absorbing layer materials prepared in Comparative Example 1 and Example 1;
[0027] Figure 5 is a comparison chart of the PL spectrum intensity of the light absorption layer materials prepared in Comparative Example 2 and Example 1;
[0028] Figure 6 is a direct band gap diagram of the light absorbing layer material prepared in Comparative Example 1;
[0029] Figure 7 is a direct band gap diagram of the light absorbing layer material obtained in Example 1;
[0030] Figure 8 This is a graph showing the fluorescence intensity of the light absorbing layer material obtained in Comparative Example 1 as a function of time;
[0031] Fig. 9 This is a graph showing the fluorescence intensity of the light-absorbing layer material prepared in Example 1 changing with time. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] The applicant of the present invention has discovered that a perovskite solar cell is composed of a transparent conductive electrode, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a counter electrode; wherein the perovskite light absorbing layer can absorb sunlight energy and generate electrons and holes when the energy is greater than its own bandgap width, and because the energy band width of the perovskite light absorbing layer is higher than that of the electron transport layer, electrons can be transferred from the perovskite light absorbing layer to the electron transport layer, and then transported to the anode and the external circuit; at the same time, the holes in the perovskite light absorbing layer are transferred to the hole transport layer, and then transported to the cathode and the external circuit.
[0034] The light-absorbing layer in existing perovskite cells is made of organic-inorganic hybrid perovskite. Although it has a high cell efficiency, its stability is poor. If inorganic perovskite materials are directly used to prepare solar cells, although the stability of the cell can be guaranteed, the photoelectric conversion efficiency of the cell will be significantly reduced. In addition, when perovskite materials are prepared in a crystallized manner, the surface inevitably contains a large number of defects. The more defects there are, the lower the photoelectric conversion efficiency of the material.
[0035] In order to solve the above problems, an embodiment of the present invention provides a solar cell light absorption layer material, wherein the light absorption layer material comprises an inorganic perovskite material and PbS quantum dots, wherein the PbS quantum dots are doped in the inorganic perovskite material.
[0036] Among them, PbS quantum dots have good optical properties and a narrow spectral width, which can convert less energy into more ambient emission light. By doping PbS quantum dots in inorganic perovskite materials, it is possible to ensure the stability of the all-inorganic perovskite material, and use PbS quantum dots to passivate surface defects, thereby improving the photoelectric conversion efficiency and further enhancing the stability of the material, thus solving the problem that existing perovskite solar cells cannot effectively balance stability and photoelectric conversion efficiency.
[0037] In the light absorbing layer material provided in the embodiment of the present invention, the doping concentration of PbS quantum dots is 50-100 mg / mL, and the band gap can be adjusted by changing the size to achieve the purpose of tuning the response band.
[0038] Optionally, in one embodiment, the doping concentration of PbS quantum dots in the light absorbing layer material is in the range of one or any two of 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, 100 mg / mL.
[0039] In the light absorbing layer material provided in the embodiment of the present invention, the perovskite is selected from all-inorganic perovskite, which can improve the stability of the perovskite light absorbing layer. Optionally, in one embodiment, the inorganic perovskite material includes one or more of CsPbCl3, CH3NH3PbI3, CsPbBr3, and RbPbI3.
[0040] The present invention also provides a method for preparing a solar cell light absorbing layer material. Figure 1 As shown, it includes steps 101 to 103:
[0041] Step 101, providing PbS quantum dots and cesium oleate precursor solutions;
[0042] Step 102, adding PbS quantum dots to the cesium oleate precursor solution, mixing, and obtaining a precursor mixed solution;
[0043] Step 103: In a protective gas atmosphere and under a heating state, inject the precursor mixed solution into a lead halide solution for reaction, and then cool, centrifuge and collect a precipitate to obtain a solar cell light absorbing layer material.
[0044] In the embodiment of the present invention, PbS quantum dots are first added to a cesium oleate precursor solution, and then a mixed solution of PbS quantum dots and cesium oleate precursor is introduced into a lead halide solution by hot injection, thereby synthesizing a CsPbCl3 / PbS quantum dot solution having a higher fluorescence quantum yield, better stability and obvious yield advantages.
[0045] In the above step 101, the synthesis method of PbS quantum dots is as follows:
[0046] PbCl2 is added to oleylamine, and reacted at 80-100°C for 10-60 minutes in a protective gas atmosphere to obtain a lead complex;
[0047] Inorganic sulfur is added to oleylamine, and then added to a lead complex at 150-300° C. in a protective gas atmosphere, reacted for 30-120 minutes, centrifuged and precipitated to obtain PbS quantum dots.
[0048] For example, 0.28 g PbCl2 and 5 mL of oleylamine are added to a 25 mL three-necked flask, heated to 90°C at a temperature gradient of 5°C / min under argon, and then maintained for 30 minutes to obtain a lead complex; 27 mg of inorganic sulfur and 2.5 mL of oleylamine are added to a 25 mL three-necked flask, heated to 90°C at a temperature gradient of 5°C / min under argon atmosphere, and then the reaction solution is added to the lead complex, and stirred and heated to 220°C under the protection of argon, and then aged for 60 minutes until the reaction is complete, at which time the solution is dark blue or black; the completely reacted solution is poured into a centrifuge tube and centrifuged at 3000 rpm for 3 minutes to take a dark blue precipitate, which is PbS quantum dots.
[0049] In the embodiment of the present invention, the PbS quantum dots are added into ethanol for easy storage.
[0050] In the above step 101, the solvent of the cesium oleate precursor solution may be octadecene, and the synthesis method of the cesium oleate precursor solution is as follows:
[0051] Oleic acid and Cs2CO3 are added to octadecene, and maintained at 100-125°C for 30-120 minutes in a protective gas atmosphere, and then reacted at 130-200°C for 1-10 minutes to obtain a cesium oleate precursor solution.
[0052] Among them, after oleic acid and Cs2CO3 are added to octadecene, the temperature is maintained at 100-125°C for 30-120 minutes in a protective gas atmosphere, which can effectively remove water and oxygen in the air.
[0053] For example, 8.0 mL of octadecene, 0.5 mL of oleic acid and 0.5 mmol of Cs2CO3 are placed in a 50 mL three-necked flask, heated to 120°C at a temperature increase gradient of 5°C / min under the condition of passing argon, and maintained for one hour; then heated to 150°C at a temperature increase gradient of 5°C / min and maintained for 5 minutes until the reaction is completed, to obtain a cesium oleate precursor solution, which is transparent in color.
[0054] In the above step 102, PbS quantum dots are added to the cesium oleate precursor solution, and the mixture is mixed by stirring or the like under heating to obtain a precursor mixed solution including PbS quantum dots and the cesium oleate precursor.
[0055] In the above step 102, the PbS quantum dots are added to the cesium oleate precursor solution at a molar ratio of 0.8 to 2.5:1, that is, the PbS quantum dots are added to the cesium oleate precursor solution at a molar ratio of PbS to cesium oleate of 0.8 to 2.5:1, which can make the luminescence spectrum bandwidth of the luminescent material narrower, thereby obtaining higher color purity.
[0056] In the above step 103, the lead halide solution can be one or more octadecene solutions of PbCl2, PbI2, PbBr2, and the solution includes oleic acid and quinolone (OLA). For example, 5 mL of octadecene, 0.5 mL of quinolone, 0.5 mL of oleic acid and 0.2 mmol PbCl2 are put into a 25 mL three-necked flask, heated to 120 ° C and maintained for 1 hour under the condition of passing argon gas, and after the solid is completely dissolved, the octadecene solution of PbCl2 is obtained.
[0057] In the above step 103, the protective gas may be argon, nitrogen, etc. By introducing the above protective gas, the impurity gas generated by the reaction can be promptly removed from the reaction system, while preventing the product from being oxidized in a heated state.
[0058] In the above step 103, the higher the reaction temperature, the higher the yield. However, if the temperature is too high, the oleic acid molecules will be over-decomposed to produce a large amount of impurities and unstable products. If the reaction time is too short, the effect will not be achieved. If the reaction time is too long, the oleic acid molecules will be over-decomposed.
[0059] Optionally, in one embodiment, in the above step 103, the heating temperature is 140-200°C, and the reaction time is 90s-150s, wherein the reaction can be carried out by heating to 140-200°C with a temperature gradient of 5aC / min under the condition of passing argon gas.
[0060] For example, the lead halide solution can be heated to 140° C. with a temperature gradient of 5 aC / min under the condition of passing argon gas, and then the precursor mixed solution is injected and maintained for 150 seconds to complete the reaction.
[0061] For example, the lead halide solution can be heated to 150° C. with a temperature gradient of 5 aC / min under the condition of passing argon gas, and then the precursor mixed solution is injected and maintained for 120 seconds to complete the reaction.
[0062] For example, the lead halide solution can be heated to 200° C. with a temperature gradient of 5aC / min under the condition of passing argon gas, and then the precursor mixed solution is injected and maintained for 90 seconds to complete the reaction.
[0063] Optionally, in one embodiment, in the above step 103, the precursor mixed solution can be injected into the lead halide solution at a ratio of (5-10 mL): (0.4-0.8 g), so as to obtain a higher luminescent color purity.
[0064] Optionally, in the above step 103, heating is stopped after reaching a preset reaction time, and cooling is performed in an ice-water bath, and the reaction is performed for 8 to 11 seconds to precipitate crystals, and then the three-necked flask is placed in an ice-water bath and quickly cooled to room temperature, thereby achieving further purification.
[0065] In the embodiment of the present invention, after the precursor mixed solution is injected into the lead halide solution and the reaction is completed, it is cooled and then placed in a centrifuge tube for centrifugal operation. The obtained precipitate is an inorganic perovskite material doped with lead halide. The rotation speed of the above centrifugal operation can be 8000-12000 rpm for 8-12 min; for example, the rotation speed of the centrifugal operation can be 8000 rpm for 12 min; for example, the rotation speed of the centrifugal operation can be 10000 rpm for 10 min; for example, the rotation speed of the centrifugal operation can be 12000 rpm for 8 min.
[0066] Optionally, in one embodiment, in the preparation method provided in the embodiment of the present invention, the above step 103 further includes:
[0067] After obtaining the precipitate, the precipitate is added into n-hexane and ultrasonically dispersed, and then centrifuged to obtain the centrifuge liquid as the solar cell light absorption layer material.
[0068] In this embodiment, n-hexane is used to dissolve CsPbX3 precipitate doped with PbS quantum dots, wherein X represents a halogen element; and then the undissolved solid impurities are removed by centrifugal operation to achieve the extraction effect. The rotation speed of the above-mentioned centrifugal operation can be 5000-7000 rpm, and the time is 6-10 minutes; for example, the rotation speed of the centrifugal operation can be 5000 rpm, and the time is 10 minutes; for example, the rotation speed of the centrifugal operation can be 6000 rpm, and the time is 8 minutes; for example, the rotation speed of the centrifugal operation can be 7000 rpm, and the time is 10 minutes.
[0069] An embodiment of the present invention further proposes a solar cell, wherein the solar cell includes a transparent conductive electrode, an electron transport layer, a light absorbing layer, a hole transport layer and a counter electrode stacked in sequence, and the light absorbing layer includes the above-mentioned solar cell light absorbing layer material.
[0070] In this embodiment, the light absorbing layer of the solar cell is made of the above-mentioned solar cell light absorbing layer material, that is, the solar cell is a perovskite cell.
[0071] For the above solar cell embodiment, its light absorbing layer includes the above light absorbing layer material and can achieve the same technical effect. To avoid repetition, it will not be described here. For relevant details, please refer to the partial description of the light absorbing layer material embodiment.
[0072] The present invention is described in detail below by way of examples.
[0073] Example 1
[0074] (1) Preparation of PbS quantum dots:
[0075] 0.28 g of PbCl2 and 5 mL of oleylamine were added to a 25 mL three-necked flask, heated to 90 °C at a temperature gradient of 5 °C / min under argon, and then maintained for 30 min to prepare a lead complex;
[0076] Add 27 mg of inorganic sulfur and 2.5 mL of oleylamine to a 25 mL three-necked flask, heat to 90 °C at a temperature gradient of 5 °C / min under an argon atmosphere, then add the reaction solution to the lead complex, stir and heat to 220 °C under the protection of argon, and then age for 60 min until the solution is dark blue or black, pour the reacted solution into a centrifuge tube, and centrifuge at 3000 rpm for 3 min, take the dark blue precipitate, which is PbS quantum dots, and add 5 mL of ethanol to it for preservation;
[0077] (2) Preparation of cesium oleate precursor:
[0078] 8.0 mL of octadecene, 0.5 mL of oleic acid and 0.5 mmol of Cs2CO3 were placed in a 50 mL three-necked flask, heated to 120°C at a temperature increase gradient of 5°C / min under the condition of passing argon gas, and maintained for one hour; then heated to 150°C at a temperature increase gradient of 5°C / min and maintained for 5 minutes until the solution became transparent, to obtain a cesium oleate precursor solution;
[0079] (3) Preparation of precursor mixed solution:
[0080] Add 0.2 g of PbS quantum dots prepared in step (1) to the cesium oleate precursor solution, and stir evenly at 150° C. for three minutes to obtain a precursor mixed solution;
[0081] (4) Preparation of solar cell light absorbing layer materials:
[0082] 5 mL of octadecene, 0.5 mL of quinolone, 0.5 mL of oleic acid and 0.2 mmol of PbCl2 were placed in a 25 mL three-necked flask, heated to 120 °C and maintained for 1 hour under the condition of passing argon gas, and a PbCl2 solution was obtained after the solid was completely dissolved;
[0083] Under the condition of passing argon, the PbCl2 solution was heated to 150°C with a temperature gradient of 5°C / min, and then 0.4 mL of the precursor mixed solution at 100°C was injected and maintained for 120 seconds, after which the heating was stopped and the mixture was cooled in an ice water bath and reacted for 10 seconds. The mixture was then placed in a centrifuge tube and centrifuged at 10000 rpm for 10 minutes to retain the precipitate;
[0084] The above precipitate was added into 10 mL of n-hexane and dispersed on an ultrasonic machine, then put into a centrifuge tube and centrifuged at 6000 rpm for 8 minutes, and the solution was retained to obtain a solar cell light absorbing layer material.
[0085] In Example 1, the prepared solar cell light-absorbing layer material is an inorganic perovskite material CsPbCl3 / PbS quantum dot solution doped with PbS quantum dots.
[0086] Example 2
[0087] The difference between Example 2 and Example 1 is that in step (4), PbCl2 is adjusted to PbBr2.
[0088] Example 3
[0089] The difference between Example 3 and Example 1 is that in step (4), PbCl2 is adjusted to PbI2.
[0090] Example 4
[0091] The difference between Example 4 and Example 1 is that in step (4), the volume of the injected precursor mixed solution is adjusted to 0.1 mL.
[0092] Example 5
[0093] The difference between Example 5 and Example 1 is that in step (4), the volume of the injected precursor mixed solution is adjusted to 8 mL.
[0094] Example 6
[0095] The difference between Example 6 and Example 1 is that in step (3), the amount of PbS quantum dots added is adjusted to 0.6 g.
[0096] Example 7
[0097] The difference between Example 7 and Example 1 is that in step (4), under the condition of passing argon gas, the PbCl2 solution is heated to 150°C with a temperature gradient of 5°C / min, and then 0.4 mL of the precursor mixed solution with a temperature of 100°C is injected and maintained for 90 seconds.
[0098] Example 8
[0099] The difference between Example 8 and Example 1 is that in step (4), under the condition of passing argon gas, the PbCl2 solution is heated to 150°C with a temperature gradient of 5°C / min, and then 0.4 mL of the precursor mixed solution with a temperature of 100°C is injected and maintained for 150s.
[0100] Example 9
[0101] The difference between Example 9 and Example 1 is that in step (4), under the condition of passing argon gas, the PbCl2 solution is heated to 150°C with a temperature gradient of 5°C / min, and then 0.4 mL of the precursor mixed solution with a temperature of 100°C is injected and maintained for 200 seconds.
[0102] Example 10
[0103] The difference between Example 10 and Example 1 is that in step (4), under the condition of passing argon gas, the PbCl2 solution is heated to 140°C with a temperature gradient of 5°C / min, and then 0.4 mL of the precursor mixed solution with a temperature of 100°C is injected and maintained for 120 seconds.
[0104] Embodiment 11
[0105] The difference between Example 11 and Example 1 is that in step (4), under the condition of passing argon gas, the PbCl2 solution is heated to 200°C with a temperature gradient of 5°C / min, and then 0.4 mL of the precursor mixed solution with a temperature of 100°C is injected and maintained for 120 seconds.
[0106] Comparative Example 1
[0107] (1) Preparation of cesium oleate precursor:
[0108] 8.0 mL of octadecene, 0.5 mL of oleic acid and 0.5 mmol of Cs2CO3 were placed in a 50 mL three-necked flask, heated to 120°C at a temperature increase gradient of 5°C / min under the condition of passing argon gas, and maintained for one hour; then heated to 150°C at a temperature increase gradient of 5°C / min and maintained for 5 minutes until the solution became transparent, to obtain a cesium oleate precursor solution;
[0109] (2) Preparation of solar cell light absorbing layer materials:
[0110] 5 mL of octadecene, 0.5 mL of quinolone, 0.5 mL of oleic acid and 0.2 mmol of PbCl2 were placed in a 25 mL three-necked flask, heated to 120 °C and maintained for 1 hour under the condition of passing argon gas, and a PbCl2 solution was obtained after the solid was completely dissolved;
[0111] Under the condition of passing argon, the PbCl2 solution was heated to 150°C with a temperature gradient of 5°C / min, and then 0.4 mL of cesium oleate precursor solution at 100°C was injected and maintained for 120 seconds, after which the heating was stopped and cooled in an ice water bath, reacted for 10 seconds, and then placed in a centrifuge tube and centrifuged at a speed of 10000 rpm for 10 minutes to retain the precipitate;
[0112] The above precipitate was added into 10 mL of n-hexane and dispersed on an ultrasonic machine, then put into a centrifuge tube and centrifuged at 6000 rpm for 8 minutes, and the solution was retained to obtain a solar cell light absorbing layer material.
[0113] In Comparative Example 1, the prepared solar cell light-absorbing layer material is an inorganic perovskite material CsPbCl3 quantum dot solution not doped with PbS.
[0114] Comparative Example 2
[0115] (1) Preparation of PbS quantum dots:
[0116] 0.28 g of PbCl2 and 5 mL of oleylamine were added to a 25 mL three-necked flask, heated to 90 °C at a temperature gradient of 5 °C / min under argon, and then maintained for 30 min to prepare a lead complex;
[0117] Add 27 mg of inorganic sulfur and 2.5 mL of oleylamine to a 25 mL three-necked flask, heat to 90 °C at a temperature gradient of 5 °C / min under an argon atmosphere, then add the reaction solution to the lead complex, stir and heat to 220 °C under the protection of argon, and then age for 60 min until the solution is dark blue or black, pour the reacted solution into a centrifuge tube, and centrifuge at 3000 rpm for 3 min, take the dark blue precipitate, which is PbS quantum dots, and add 5 mL of ethanol to it for preservation;
[0118] (2) Preparation of cesium oleate precursor:
[0119] 8.0 mL of octadecene, 0.5 mL of oleic acid and 0.5 mmol of Cs2CO3 were placed in a 50 mL three-necked flask, heated to 120°C at a temperature increase gradient of 5°C / min under the condition of passing argon gas, and maintained for one hour; then heated to 150°C at a temperature increase gradient of 5°C / min and maintained for 5 minutes until the solution became transparent, to obtain a cesium oleate precursor solution;
[0120] (3) Preparation of solar cell light absorbing layer materials:
[0121] 5 mL of octadecene, 0.5 mL of quinolone, 0.5 mL of oleic acid and 0.2 mmol of PbCl2 were placed in a 25 mL three-necked flask, heated to 120 °C and maintained for 1 hour under the condition of passing argon gas, and a PbCl2 solution was obtained after the solid was completely dissolved;
[0122] Under the condition of passing argon, the PbCl2 solution was heated to 150°C with a temperature gradient of 5°C / min, and then 0.4 mL of cesium oleate precursor solution at 100°C was injected and maintained for 120 seconds, after which the heating was stopped and cooled in an ice water bath, reacted for 10 seconds, and then placed in a centrifuge tube and centrifuged at a speed of 10000 rpm for 10 minutes to retain the precipitate;
[0123] The above precipitate was added to 10 mL of n-hexane, and then 0.2 g of the PbS quantum dots in step (1) were added and dispersed on an ultrasonic machine. The mixture was then placed in a centrifuge tube and centrifuged at 6000 rpm for 8 min. The solution was retained to obtain an inorganic perovskite material mixed with PbS quantum dots.
[0124] In Comparative Example 2, the prepared solar cell light-absorbing layer material is an inorganic perovskite material CsPbCl3-PbS quantum dot solution mixed with PbS.
[0125] The perovskite materials prepared in Comparative Example 1 and Example 1 were subjected to lattice structure analysis, and the results were as follows: Figure 2 and 3As shown, it is illustrated that the preparation method provided by the embodiment of the present invention can dope PbS quantum dots into the perovskite CsPbCl3.
[0126] At the same concentration, the PL spectrum intensity of the inorganic perovskite materials prepared in Comparative Example 1 and Example 1 was measured respectively, and the results are as follows: Figure 4 As shown, by comparison, it can be seen that the fluorescence intensity of the CsPbCl3 / PbS quantum dot solution is higher. The results confirm that embedding PbS quantum dots into the CsPbCl3 quantum dot solution can passivate the CsPbCl3 surface to improve its photoelectric properties.
[0127] At the same concentration, the PL spectrum intensity of the inorganic perovskite materials prepared in Comparative Example 2 and Example 1 was measured respectively, and the results are as follows: Figure 5 As shown, by comparison, it can be seen that the fluorescence intensity of the CsPbCl3 / PbS quantum dot solution is higher. The results confirm that embedding PbS quantum dots into the CsPbCl3 quantum dot solution can passivate the CsPbCl3 surface to improve its photoelectric properties; while a simple mixing operation cannot play a passivation role.
[0128] At the same concentration, the direct band gap lengths of the inorganic perovskite materials prepared in Comparative Example 1 and Example 1 were measured according to the UV spectrum, and the results were as follows: Figure 6 and 7 As shown, it can be seen that the direct band gap width of CsPbCl3 is 3.18eV, while the direct band gap width of CsPbCl3 / PbS is 3.07eV, indicating that the inorganic perovskite material doped with lead sulfide has a narrower band gap, which can reduce the recombination probability of non-radiative transition channels, and has a higher fluorescence quantum yield and a larger absorption coefficient.
[0129] In addition, the photoelectric conversion efficiency and fluorescence lifetime of the inorganic perovskite materials prepared in each embodiment and comparative example were measured, and the results are shown in Table 1.
[0130] Table 1
[0131]
[0132]
[0133] The fluorescence intensity of the inorganic perovskite materials prepared in Comparative Example 1 and Example 1 changes with time as shown in the following table: Figure 8 and 9As shown; it can be seen that the fluorescence lifetime of CsPbCl3 undoped with lead sulfide is 3.83ns, while the fluorescence lifetime of CsPbCl3 / PbS is 4.15ns, indicating that PbS can reduce the probability of surface carrier recombination and passivate the surface of CsPbCl3, thereby improving its luminescence properties and stability, thereby extending the fluorescence lifetime of CsPbCl3.
[0134] In summary, in the embodiment of the present invention, the solar cell light absorption layer material provided comprises an inorganic perovskite material and PbS quantum dots, wherein the PbS quantum dots are doped in the inorganic perovskite material. Because the PbS quantum dots have good optical properties and a narrow spectral width, less energy can be converted into more ambient emission light. By doping the inorganic perovskite material with PbS quantum dots, the stability of the all-inorganic perovskite material can be ensured, and the surface defects can be passivated by using the PbS quantum dots, thereby improving the photoelectric conversion efficiency and further enhancing the stability of the material, thereby solving the problem that the existing perovskite solar cells cannot effectively take into account both stability and photoelectric conversion efficiency.
[0135] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0136] The above is a detailed introduction to a solar cell light-absorbing layer material, a preparation method and a battery provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technicians in this field, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A solar cell light-absorbing layer material, characterized in that: The components constituting the light absorption layer material include inorganic perovskite material and PbS quantum dots, and the PbS quantum dots are doped in the inorganic perovskite material.
2. The light absorbing layer material according to claim 1, characterized in that: In the light absorption layer material, the doping concentration of the PbS quantum dots is 50-100 mg / mL.
3. The light absorbing layer material according to claim 1 or 2, characterized in that: The inorganic perovskite material includes one or more of CsPbCl3, CH3NH3PbI3, CsPbBr3, and RbPbI3.
4. A method for preparing a solar cell light-absorbing layer material, characterized in that: include: Provide PbS quantum dots and cesium oleate precursor solutions; Adding PbS quantum dots to the cesium oleate precursor solution and mixing well to obtain a precursor mixed solution; In a protective gas atmosphere and under a heating state, the precursor mixed solution is injected into a lead halide solution for reaction, and then cooled, centrifuged and precipitated to obtain a solar cell light absorption layer material.
5. The preparation method according to claim 4, characterized in that: The heating temperature is 140-200° C., and the reaction time is 90s-150s.
6. The preparation method according to claim 4, characterized in that: The protective gas is argon.
7. The preparation method according to claim 4, characterized in that: The PbS quantum dots are added to the cesium oleate precursor solution at a molar ratio of 0.8 to 2.5:
1.
8. The preparation method according to claim 5, characterized in that: Before the precursor mixed solution is injected into the lead halide solution for reaction, the lead halide solution is heated to 140-200° C. with a temperature increase gradient of 2-10° C. / min.
9. The preparation method according to claim 4, characterized in that: After obtaining the precipitate, the method further comprises: The precipitate is added into n-hexane and ultrasonically dispersed, and then centrifuged to obtain the centrifuge liquid as the solar cell light absorption layer material.
10. A solar cell, characterized in that: The invention comprises a transparent conductive electrode, an electron transport layer, a light absorbing layer, a hole transport layer and a counter electrode which are stacked in sequence, wherein the light absorbing layer comprises the solar cell light absorbing layer material as claimed in any one of claims 1 to 3.